2001
DOI: 10.1210/mend.15.7.0671
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulation of Estrogen Receptor Conformation by Different Estrogen Response Elements

Abstract: Estrogen-regulated gene expression is dependent on interaction of the estrogen receptor (ER) with the estrogen response element (ERE). We assessed the ability of the ER to activate transcription of reporter plasmids containing either the consensus vitellogenin A2 ERE or the imperfect pS2, vitellogenin B1, or oxytocin (OT) ERE. The A2 ERE was the most potent activator of transcription. The OT ERE was significantly more effective in activating transcription than either the pS2 or B1 ERE. In deoxyribonuclease I (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
53
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 48 publications
6
53
1
2
Order By: Relevance
“…These experiments combined with our GST-MPG pull-down studies indicate that ERE-containing DNA increases the interaction of ER␣ with MPG. We have previously demonstrated that DNA acts as an allosteric modulator of ER␣ conformation and thereby influences the interaction of the receptor with coregulatory proteins (5,25,27). Our current studies suggest that the interaction of the receptor with the ERE enhances the recruitment of MPG to estrogen-responsive genes.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…These experiments combined with our GST-MPG pull-down studies indicate that ERE-containing DNA increases the interaction of ER␣ with MPG. We have previously demonstrated that DNA acts as an allosteric modulator of ER␣ conformation and thereby influences the interaction of the receptor with coregulatory proteins (5,25,27). Our current studies suggest that the interaction of the receptor with the ERE enhances the recruitment of MPG to estrogen-responsive genes.…”
supporting
confidence: 50%
“…Pull-down Assay-Pull-down assays were carried out by adsorbing 200 pmol of annealed biotinylated oligos containing the A2 ERE or a nonspecific DNA sequence to streptavidin-agarose beads as described (25). The immobilized DNA was incubated with 400 pmol of baculovirus-expressed, purified ER␣ in the presence of 1 M 17␤-estradiol (E 2 ) for 10 min followed by addition of 500 g of HeLa nuclear extract prepared as described (25).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA Pulldown Assays-Pulldown assays were carried out as described (32) using biotinylated oligonucleotides containing the vitellogenin A2 ERE (33) or a nonspecific sequence (33) or the cyclin G2 promoter sequence (5Ј-/Bio/CGTCCCCCTCCTCGGCACCAGTC-CAGGCCGGTCGCG), a cyclin G2 promoter sequence with mutated half-ERE or a sequence containing only a half-ERE but no Sp1 binding sites (5Ј-/Bio/CTAGATTACTTCTCATGTTAGTTCTACTGACCA-CTAGATTACTTCTCATGTTAGCC), which were synthesized by Integrated DNA Technologies, Coralville, IA. Each annealed oligonucleotide (200 pmol) was adsorbed on to streptavidin-agarose beads (Pierce).…”
Section: Methodsmentioning
confidence: 99%